The thermal diffusivity of molecular cryocrystals - Sumarokov, V.V.; Jeżowski, A.; Stachowiak, P.; Freiman, Y.A. (Физика низких температур, 2019)
Low-temperature thermal diffusivity of molecular cryocrystals (O₂, N₂, CO, N₂O and CO₂) has been investigated and some anomalies were found. The thermal diffusivity of these crystals vary by more than 4–6 orders of
the magnitude in the temperature range from 1 K up to their triple points. The thermal diffusivity displays jumps
at the phase transition points. It has been found that the thermal diffusivity of solid oxygen is nonmonotonic. Below 4 K, the temperature dependence shows a plateau which is due to the fact that both the heat capacity and the
thermal conductivity have the cubic temperature dependence in this temperature range. For the cryocrystals of
the nitrogen group, a similar plateau is shifted to lower temperatures. The temperature dependence of the equalization time for these crystals is studied. Досліджено низькотемпературну температуропровідність
молекулярних кріокристалів (O₂, N₂, CO, N₂O і CO₂).
Температуропровідність цих кристалів змінюється більш ніж
на 4–6 порядків в області температур від 1 К до їх потрійних
точок. В області фазових перетворень спостерігаються стрибки температуропровідності. Виявлено, що температуропровідність твердого кисню є немонотонною. Нижче 4 К на
температурній залежності спостерігається плато, яке обумовлено тим, що як теплоємність, так і теплопровідність в цьому
температурному діапазоні мають кубічну температурну залежність. Для кріокристалів азотної групи подібне плато зміщується в бік більш низьких температур. Вивчено температурну
залежність часів вирівнювання температури для цих кристалів. Исследована низкотемпературная температуропроводность
молекулярных криокристаллов (O₂, N₂, CO, N₂O и CO₂). Температуропроводность этих кристаллов изменяется более чем
на 4–6 порядков в области температур от 1 К до их тройных
точек. В области фазовых переходов наблюдаются скачки температуропроводности. Обнаружено, что температуропроводность твердого кислорода является немонотонной. Ниже 4 К на
температурной зависимости наблюдается плато, обусловленное
тем, что как теплоемкость, так и теплопроводность в этом температурном диапазоне имеют кубическую температурную зависимость. Для криокристаллов азотной группы подобное плато смещается в сторону более низких температур. Изучена
температурная зависимость времен выравнивания температуры
для этих кристаллов.